2014
DOI: 10.1055/s-0034-1371513
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Intrathecal Caffeic Acid Phenethyl Ester and Methylprednisolone on Oxidant/Antioxidant Status in Traumatic Spinal Cord Injuries

Abstract: Intrathecal injection of both CAPE and MP inhibits lipid peroxidation and increase of oxidants in SCIs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 29 publications
1
3
0
Order By: Relevance
“…ROS is a collective term that broadly describes O 2 -derived free radicals that can induce extrinsic apoptosis through the activation of JNK or attack DNA directly (reviewed in [25,26]). We and others have demonstrated the potential of CAPE structures to modulate the cell’s redox state [48,49,50]. We also observe that 10 is among the weakest antioxidants in our panel of analogs, suggesting a pro-oxidative potential that sensitizes cancer cells to extrinsic apoptotic events.…”
Section: Resultssupporting
confidence: 63%
“…ROS is a collective term that broadly describes O 2 -derived free radicals that can induce extrinsic apoptosis through the activation of JNK or attack DNA directly (reviewed in [25,26]). We and others have demonstrated the potential of CAPE structures to modulate the cell’s redox state [48,49,50]. We also observe that 10 is among the weakest antioxidants in our panel of analogs, suggesting a pro-oxidative potential that sensitizes cancer cells to extrinsic apoptotic events.…”
Section: Resultssupporting
confidence: 63%
“…In experimental SCI models related to quercetin, a flavonoid, the neuroprotective effect of this agent was shown based on reduced MDA and increased TAS levels. [33] In an experimental SCI study, Gocmez et al [34] performed an intrathecal injection of caffeic acid, a phenol component, and showed that it inhibited lipid peroxidation and the increase of oxidants.…”
Section: Discussionmentioning
confidence: 99%
“…To examine the role of nuclear factor‐κB (NF‐κB) in stress‐caused effect, an NF‐κB inhibitor caffeic acid phenethyl ester (CAPE, 50 μM, 50 μL; Selleck) was given at the start of WAS and continuously i.t. administered via an osmotic minipump 25 …”
Section: Methodsmentioning
confidence: 99%